Activation of Type I and III interferon signalling pathways occurs in lung epithelial cells infected with low pathogenic Avian influenza viruses - Sugrue, Richard J. (2013)
The host response to the low pathogenic avian influenza (LPAI) H5N2, H5N3 and H9N2 viruses were examined in A549, MDCK, and CEF cells using a systems-based approach. The H5N2 and H5N3 viruses replicated efficiently in A549 and MDCK cells, while the H9N2 virus replicated least efficiently in these cell types. However, all LPAI viruses exhibited similar and higher replication efficiencies in CEF cells. A comparison of the host responses of these viruses and the H1N1/WSN virus and low passage pH1N1 clinical isolates was performed in A549 cells. The H9N2 and H5N2 virus subtypes exhibited a robust induction of Type I and Type III interferon (IFN) expression, sustained STAT1 activation from between 3 and 6 hpi, which correlated with large increases in IFN-stimulated gene (ISG) expression by 10 hpi. In contrast, cells infected with the pH1N1 or H1N1/WSN virus showed only small increases in Type III IFN signalling, low levels of ISG expression, and down-regulated expression of the IFN type I receptor. JNK activation and increased expression of the pro-apoptotic XAF1 protein was observed in A549 cells infected with all viruses except the H1N1/WSN virus, while MAPK p38 activation was only observed in cells infected with the pH1N1 and the H5 virus subtypes. No IFN expression and low ISG expression levels were generally observed in CEF cells infected with either AIV, while increased IFN and ISG expression was observed in response to the H1N1/WSN infection. These data suggest differences in the replication characteristics and antivirus signalling responses both among the different LPAI viruses, and between these viruses and the H1N1 viruses examined. These virus-specific differences in host cell signalling highlight the importance of examining the host response to avian influenza viruses that have not been extensively adapted to mammalian tissue culture.